Quench calculations for the superconducting dipole magnet of CBM experiment at FAIR. (August 2016) - Kurilkin, P.; Akishin, P.; Bychkov, A.; Floch, E.; Gusakov, Yu.; Ladygin, V.; Malakhov, A.; Moritz, G.; Ramakers, H.; Senger, P.; Shabunov, A.; Szwangruber, P.; et al.
Abstract: The scientific mission of the Compressed Baryonic Matter (CBM) experiment is the study of the nuclear matter properties at the high baryon densities in heavy ion collisions at the Facility of Antiproton and Ion Research (FAIR) in Darmstadt. The 5.15 MJ superconducting dipole magnet will be used in the silicon tracking system of the CBM detector. It will provide a magnetic field integral of 1 Tm which is required to obtain a momentum resolution of 1% for the track reconstruction. This paper presents quench modeling and evaluation of candidate protection schemes for the CBM dipole magnet. Two quench programs based on finite-difference method were used in simulation. One of them is currently used at GSI, and the other based on CIEMAT (Madrid, Spain) was modified to perform quench calculation for the CBM magnet.